Outcome after Repair of Concurrent Upper and Lower Canalicular Lacerations. (June 2014) - Ejstrup, Rasmus; Wiencke, Anne K.; Toft, Peter B.
Abstract Purpose: To investigate the functional and cosmetic results after primary surgical repair of bicanalicular lacerations. Methods: We identified patients diagnosed with bicanalicular lacerations at the Eye Clinic of Rigshospitalet, Copenhagen from 2000 through 2009. Patient charts were reviewed and a telephone interview was conducted according to a standard questionnaire, regarding tearing and cosmesis. Symptoms (no epiphora, epiphora only when outdoors, epiphora when indoors, or epiphora with discharge) were compared to the healthy eye and scarring was graded from 0 to 10 by the patient (none to very disturbing). Results: Fifteen patients had bicanalicular lacerations. Canalicular silicone stents were used in six different ways: two monostents to the lacrimal sac (n = 1), one monostent to the nose in the upper canaliculus (n = 2), two monostents to the nose (n = 2), bicanalicular stent to the nose (n = 7), bicanalicular anular stent (n = 2), bicanalicular stent and dacryocystorhinostomy (n = 1). The surgery was carried out by 6 different surgeons. Eleven patients could be followed up. In these, epiphora was reported after primary surgery by 7 patients, and scarring was graded to more than 1 in 4 patients. However, it is noteworthy that 3 of 4 patients operated with monostents had no symptoms; the fourth patient reported having epiphora indoors. Furthermore, the four patients operated with monostents graded their scaring to be 0 (n = 3) or 1 (n = 1) only. Conclusion: Sequelae are common after bicanalicular lacerations. The use of one or two monostents to the nose appears to be a reasonable alternative to the traditional use of one bicanalicular stent.